2003
DOI: 10.3928/0098-9134-20031201-08
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure in Older Adults: Providing Nursing Care to Improve Outcomes

Abstract: Heart failure continues to be a challenge for older patients and their health care providers. This article is based on work by advanced practice nurses in a nursing study funded by the National Institute of Nursing Research of the National Institute of Health. Mary Naylor, RN, PhD at the University of Pennsylvania School of Nursing through grant #1RO1-NR04315 is using a transitional care model to provide advance practice nurse intervention for older adults with heart failure in a randomized controlled trial. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Study subjects have included some of the most vulnerable elders, including those with complex comorbid conditions, and in a recent, randomized controlled trial, elders with cognitive impairment and their CGs, whose experiences were used for the analysis described in this article (M. D. Naylor et al, 2010). Findings from studies examining the APN-directed TMC and collaboration and consultation with national policy leaders have demonstrated that although the TCM consistently results in improved patient outcomes and reduced health care costs, greater clarity is needed about the specific factors and interventions that produce or inhibit quality outcomes (Bixby, Konick-McMahan, & McKenna, 2000;Brooten et al, 2002;Konick-McMahan, Bixby, & McKenna, 2003;McCauley, Bixby, & Naylor, 2006;M. D. Naylor, Hirschman, et al, 2007;M.…”
Section: Transitional Carementioning
confidence: 99%
“…Study subjects have included some of the most vulnerable elders, including those with complex comorbid conditions, and in a recent, randomized controlled trial, elders with cognitive impairment and their CGs, whose experiences were used for the analysis described in this article (M. D. Naylor et al, 2010). Findings from studies examining the APN-directed TMC and collaboration and consultation with national policy leaders have demonstrated that although the TCM consistently results in improved patient outcomes and reduced health care costs, greater clarity is needed about the specific factors and interventions that produce or inhibit quality outcomes (Bixby, Konick-McMahan, & McKenna, 2000;Brooten et al, 2002;Konick-McMahan, Bixby, & McKenna, 2003;McCauley, Bixby, & Naylor, 2006;M. D. Naylor, Hirschman, et al, 2007;M.…”
Section: Transitional Carementioning
confidence: 99%
“…These symptoms may include edema of the lower extremities and/or weight gain, shortness of breath at rest and/or increased respirations, and/or pulmonary crackles or rales. Jugular vein distention and increased abdominal girth may also be present 13 . Compliance was defined as “an active, intentional, and responsible process of care, in which the individual works to maintain his or her health in close collaboration with health care personnel.” 14 Compliance with HF regimens was operationally defined as the sum score on a revised form of the Heart Failure Compliance Questionnaire (HFCQR).…”
Section: Definition Of Termsmentioning
confidence: 99%
“…Already, more than 14 million older Americans are reporting chronic conditions such as heart disease (U.S. Census Bureau, 2006). Heart failure is now the leading cause of hospitalization among older adults (Konick-McMahan & McKenna, 2003). The challenges of implementing practice change in this already burdened industry is also discussed.…”
mentioning
confidence: 99%